Swarm intelligence foundation, principles, and engineering applications - Sharma, Abhishek (CRC Press, 2022)
"Swarm intelligence is one of the fastest-growing sub-fields of artificial intelligence and soft computing. This field includes multiple optimization algorithms to solve NP-hard problems for which conventional methods are not effective. It inspires researchers in engineering sciences to learn theories from nature and incorporate them. Swarm Intelligence: Foundation, Principles, and Engineering Applications provides a comprehensive review of new swarm intelligence techniques and offers practical implementation of Particle Swarm Optimization (PSO) with MATLAB code. The book discusses the statistical analysis of swarm optimization techniques so that researchers can analyze their experiment design. It also includes algorithms in social sectors, oil and gas industries, and recent research findings of new optimization algorithms in the field of engineering describing the implementation in Machine Learning. This book is written for students of engineering, research scientists, and academicians involved in the engineering sciences"--
Includes bibliographical references and index. - Description based on print version record and CIP data provided by publisher
Keywords: Swarm intelligence; TECHNOLOGY / Manufacturing; COMPUTERS / Artificial Intelligence